Limites e possibilidades da legislação urbanística e ambiental na bacia hidrográfica Guaranhuns, em Vila Velha/ES - Berrêdo, Eduarda Dias de (2018)
This research aims to analyze urban and environmental situation of the Guaranhuns watershed, in Vila Velha/ES, through legislation on the Areas of Permanent Preservation (APP), in order to identify challenges and possibilities for its preservation, given